15.0k views
0 votes
What is a rule for the nth term of Geometric sequence -3,-6,-12,-24,-48

What is a rule for the nth term of Geometric sequence -3,-6,-12,-24,-48-example-1

1 Answer

5 votes

The sequence is given as,


-3,\text{ -6, -12, -24, -48.......}

For the given sequence,


\begin{gathered} First\text{ term\lparen a\rparen = -3} \\ Common\text{ ratio\lparen r\rparen = }(-6)/(-3)=\text{ 2} \end{gathered}

nth term of a geometric progression is given as,


a_n\text{ = ar}^(n-1)

Where,

a = First term

r = common ratio

Therefore the nth term is calculated as,


a_n=\text{ -3\lparen2\rparen}^(n-1)

Thus the required answer is,


a_n=\text{ -3\lparen2\rparen}^(n-1)

User Tuere
by
5.0k points